2018
DOI: 10.1159/000484514
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Protein C Global Assay Levels in Infertile Women with in vitro Fertilization Failure: A Pilot Study

Abstract: Protein C global is a global dotting assay that evaluates abnormalities in the protein C anticoagulant pathway. A few studies have examined this assay in relation to assisted reproductive technology (ART), but its role in infertile women with in vitro fertilization (IVF) failure remains unclear. In this study, we assessed protein C in infertile women with a history of IVF failure who were undergoing ART. We examined 45 healthy fertile women who conceived naturally, and 45 infertile women with 2 or more implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
(37 reference statements)
0
5
1
Order By: Relevance
“…Some studies indicate that the levels of protein C were low in infertile women who underwent IVF cycles. [11][12][13]17 When comparing the prevalence of protein C deficiency among women with history of abortions in other studies, we found that the prevalence in our study is higher than some previous studies, and it is also lower than others. 11,12,17,18 This disparity in the prevalence of protein C deficiency may be due to differences in the sample size, the inclusions' criteria of the patients or the types of protein C assay.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Some studies indicate that the levels of protein C were low in infertile women who underwent IVF cycles. [11][12][13]17 When comparing the prevalence of protein C deficiency among women with history of abortions in other studies, we found that the prevalence in our study is higher than some previous studies, and it is also lower than others. 11,12,17,18 This disparity in the prevalence of protein C deficiency may be due to differences in the sample size, the inclusions' criteria of the patients or the types of protein C assay.…”
Section: Discussioncontrasting
confidence: 51%
“…Although the test of protein C has been evaluated in different samples of women with RPL, and women with recurrent IVF failure, very few studies has evaluated protein C levels in relation to the success or failure of IVF. [11][12][13]19 Another significant finding in this study showed that the level of protein C affects the results of IVF cycles' outcomes. This is compatible with the findings of El Masry el al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in their study, the results of the thrombin generation assay and TEG before the start of IVF were not associated with IVF outcomes [42]. In another paper by El Masry and colleagues [4], it was shown that women who had a negative outcome have a more pronounced decrease in protein C activity than women who became pregnant, which also points to the connection between the initially present procoagulant disorder and a negative IVF outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Infertility in women is often accompanied by a hypercoagulable state. The rates of thrombophilia [1,2] and circulating microvesicle concentrations [3] are higher and protein C activity is lower [4] in women with conception problems. In vitro fertilization (IVF) can enhance these procoagulant changes in infertile women mostly as a result of high-dose hormonal therapy.…”
Section: Introductionmentioning
confidence: 99%